Biological basis for functional cure of chronic hepatitis B. Issue 7 (29th March 2019) - Martinez, Maria G.; Testoni, Barbara; Zoulim, Fabien
Summary: Chronic hepatitis B (CHB) infection affects over 250 millon people worldwide and 800000 are expected to die yearly due to the development of hepatocellular carcinoma (HCC). Current antiviral therapies include nucleoside analogs (NAs) that target the viral retrotranscriptase inhibiting de novo viral production. Pegylated interferon (Peg‐IFN) is also effective in reducing the viral DNA load in serum. However, both treatments remain limited to control the infection, aiming for viral suppression and improving the quality of life of the infected patients. Complete cure is not possible due to the presence of the stable DNA intermediate covalently closed circular DNA (cccDNA). Attempts to achieve a functional cure are thus ongoing and novel targets and molecules, together with different combination therapies are currently in the pipeline for early clinical trials. In this review we discuss novel treatments both targeting directly and indirectly cccDNA. As we gain knowledge in the Hepatitis B virus (HBV) transcriptional control, and newer technologies emerge that could potentially allow the destruction of cccDNA, exciting new possibilities for curative therapies are discussed.